2019
DOI: 10.31487/j.cor.2019.06.16
|View full text |Cite
|
Sign up to set email alerts
|

Area Dose Response of Prevalent Childhood Thyroid Cancers after the Fukushima Nuclear Power Plant Accident

Abstract: Background and Methods: After the Fukushima Nuclear Power Plant accident, thyroid ultrasound screening was carried out on all residents of ages≤18 years at the accident. In order to find the cause for thyroid cancer prevalence, area dose dependence of childhood thyroid cancer proportion in the first and second round screening (E-I, E-II), and in 6 years as a whole (E-I+II) was analyzed for external dose estimated by Fukushima Health Management Survey and effective dose estimated by UNSCEAR. The results were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Cancers that grow more than 5 mm in diameter over a 2-year period, such as those childhood thyroid cancers detected in second-round screening in Fukushima, fall outside the category of overdiagnosis [8]. This has also been reported by Kato [59,60], Yamamoto et al [61], and Toki et al [62] However, the SHAMISEN review paper [5] erroneously indicates that no radiationrelated risks were demonstrated in those papers [59][60][61][62].…”
Section: Lessons Learned From Fukushimamentioning
confidence: 93%
“…Cancers that grow more than 5 mm in diameter over a 2-year period, such as those childhood thyroid cancers detected in second-round screening in Fukushima, fall outside the category of overdiagnosis [8]. This has also been reported by Kato [59,60], Yamamoto et al [61], and Toki et al [62] However, the SHAMISEN review paper [5] erroneously indicates that no radiationrelated risks were demonstrated in those papers [59][60][61][62].…”
Section: Lessons Learned From Fukushimamentioning
confidence: 93%
“…Three research groups showed associations between area dose and thyroid cancer incidence in the 2nd round and the 1st +2nd round [6][7][8][9]. Kato found high associations between ares dose and childhood thyroid cancer in the 2nd and 1st+2nd rounds [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…Fukushima with the prevalence of low birth weight (< 2500 g). Therefore, previously reported epidemiological health detriment after Fukushima [31][32][33][34][35][36][37]53] can be generalized and corroborated.…”
Section: Our Investigation Disclosed a Positive Association Between Tmentioning
confidence: 54%